Review of nature-based solutions in dryland ecosystems: the aral sea case study - Alikhanova, S; Bull, JW (Springer, 2023)
NbS have gained substantial attention in the academic literature recently as a potential approach for simultaneously tackling environmental issues and addressing societal challenges. Drylands, which are among the world’s most vulnerable areas to the impacts of climate change and cover a little less than the half of the global terrestrial surface, were the focus of this study. We conducted a systematic literature review to explore the potential opportunities for the application of NbS in rural drylands across the globe. We go on to specifically consider the possibility of applying selected NbS approaches in the Aral Sea region of Uzbekistan, as a case study of a dryland ecosystem illustrating major environmental and social challenges. We highlight which NbS show the most promise in the Aral Sea region and conclude with a discussion of existing gaps in the literature on NbS in drylands, and opportunities for further research.